Exploiting Phagocytic Checkpoints in Nanomedicine: Applications in Imaging and Combination Therapies - Landry, Madeleine R.; Walker, Joshua M.; Sun, Conroy (Frontiers in Chemistry, 2021)
Recent interest in cancer immunotherapy has largely been focused on the adaptive immune system, particularly adoptive T-cell therapy and immune checkpoint blockade (ICB). Despite improvements in overall survival and progression-free survival across multiple cancer types, neither cell-based therapies nor ICB results in durable disease control in the majority of patients. A critical component of antitumor immunity is the mononuclear phagocyte system and its role in both innate and adaptive immunity. The phagocytic functions of these cells have been shown to be modulated through multiple pathways, including the CD47-SIRPα axis, which is manipulated by cancer cells for immune evasion. In addition to CD47, tumors express a variety of other “don’t eat me” signals, including beta-2-microglobulin and CD24, and “eat me” signals, including calreticulin and phosphatidylserine. Therapies targeting these signals can lead to increased phagocytosis of cancer cells; however, because “don’t eat me” signals are markers of “self” on normal cells, treatment can result in negative off-target effects, such as anemia and B-cell depletion. Recent preclinical research has demonstrated the potential of nanocarriers to synergize with prophagocytic therapies, address the off-target effects, improve pharmacokinetics, and codeliver chemotherapeutics. The high surface area-to-volume ratio of nanoparticles paired with preferential size for passive targeting allows for greater accumulation of therapeutic cargo. In addition, nanomaterials hold promise as molecular imaging agents for the detection of phagocytic markers. This mini review highlights the unique capabilities of nanotechnology to expand the application and efficacy of immunotherapy through recently discovered phagocytotic checkpoint therapies.